DAMPAK PENGUMUMAN COVID-19 TERHADAP ABNORMAL STOCK RETURN DAN TRADING VOLUME ACTIVITY - Nadya, Ria Cindy; Agustiningsih, Wulandari (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This study aims to determine the impact of the announcement of COVID-19 on abnormal stock returns and trading volume activity. The variables were abnormal return and trading volume activity in 61 days, 30 days before and after the incident, and the day the COVID-19 incident occurred. This research is an event study. This study uses secondary data, namely the daily stock price and the active trading volume of each infrastructure company during the study period. The data analysis method used is the paired sample t-test and Wilcoxon signed rank test to determine the significant impact before and after the announcement of COVID-19. This study shows that there is no significant abnormal return, and the average abnormal return before the announcement of COVID-19 is smaller than after the announcement of COVID-19. There is significant trading volume activity on the day of the announcement of COVID-19 in the infrastructure sector in Indonesia, and the average trading volume activity before the announcement of COVID-19 is smaller than after the announcement of COVID-19.